Pengaruh Sertifikasi Halal dan Harga Terhadap Kepuasan Pelanggan Pada Resto Tungkal Seafood Kota Jambi - Rintan Wulandari; Addiarrahman Addiarrahman; Syamsuddin Syamsuddin (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This research aims to determine the effect of halal certification and price on customer satisfaction. This research uses a quantitative approach to collect data using primary data and questionnaires. Tungkal Seafood restaurant consumers are the subjects of this research. Purposive sampling technique, which was used to achieve the research objectives, collected 100 respondents. Normality, multicollinearity and heteroscedasticity tests are the multiple linear regression analysis tools used. The F test and T test are used to test the hypothesis. Results obtained from the regression equation: Y = 0.959+ 0.384(X1) + 0.395(X2) + e. The results of data analysis show that the independent variable halal certification (X1) does not partially influence customer satisfaction (Y) (T test), and the price variable (X2) influences customer satisfaction significantly. Simultaneously, the F test shows that the independent variables halal certification (X1) and price (X2) influence purchasing decisions (Y) positively and significantly. The influence of the Coefficient of Determination variable is 48.4%, the influence of Halal Certification and Price on Customer Satisfaction at Tungkal Seafood Resto, while 51.6% is determined by other variables outside the research.